2008
DOI: 10.1016/j.jcorpfin.2008.09.005
|View full text |Cite
|
Sign up to set email alerts
|

The determinants of board composition in a transforming economy: Evidence from Russia

Abstract: Using a unique dataset of 730 joint-stock companies, we studied the determinants of corporate board composition in Russia. Despite the widespread image of insider control in the 1990s, a large number of Russian companies now actively appoint outsider directors to monitor top management. The findings reported in this paper strongly suggest that the theories and empirical methods of financial and organizational economics help to pinpoint the factors affecting the extent of outsider directorship. We also found th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
42
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(52 citation statements)
references
References 54 publications
8
42
2
Order By: Relevance
“…Further, the findings are also in line with other studies in the tourism and hospitality for instance Adams et al [1] and Iwasaki [13]. Based on the findings, it is also noted that previous studies have confirmed that corporate governance determines the performance of the cooperatives.…”
Section: To Examine Whether the Board Of Directors Aware Of Corporatesupporting
confidence: 91%
See 2 more Smart Citations
“…Further, the findings are also in line with other studies in the tourism and hospitality for instance Adams et al [1] and Iwasaki [13]. Based on the findings, it is also noted that previous studies have confirmed that corporate governance determines the performance of the cooperatives.…”
Section: To Examine Whether the Board Of Directors Aware Of Corporatesupporting
confidence: 91%
“…Further, Adams and Mehran [1] and Dalton and Dalton [6] suggested that better performance is associated with large boards. Few studies have also emphasized the roles of Boards of Directors in cooperatives governance within the tourism and hospitality industry [1,13]. However, there has been no study concerning the budget hotel and accommodation cooperatives within the context of Malaysia.…”
Section: Problem Statement Of the Studymentioning
confidence: 99%
See 1 more Smart Citation
“…14 We cannot advance in addressing this problem because the data at hand contain no reliable instruments for key corporate governance variables. Still, our analysis is an improvement over many studies of emerging markets based on cross-sectional data (e.g., Iwasaki 2008 andBlack et al 2012).been assembled from the SKRIN and SPARK databases (www.skrin.ru, http://spark.interfax.ru) which collect and process original reports submitted by Russian joint-stock companies to the FFMS and statistical agencies. We use second quarter reports (usually prepared by companies in early July), which ensures that the data reflect the results of general shareholder meetings held at the beginning of each year (e.g., the appointment of new CEOs, boards of directors, etc.…”
Section: Data and Samplementioning
confidence: 99%
“…We lag all variables one year to reduce endogeneity problems. 9 Prior research suggests that board independence, as measured by the percentage of independent directors, can improve corporate governance although its effectiveness depends on the business and regulatory compliance environment (Hermalin and Weisbach, 2003;Xie et al, 2003;Berghe and Baelden, 2005;Iwasaki, 2008;Cornett et al, 2009). According to China's laws, independent directors are supposed to act in a similar way to those in the U.S.…”
Section: Governance Variablesmentioning
confidence: 99%